1985
DOI: 10.1159/000183370
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hemodialysis on Plasma and Erythrocyte Phenylalanine Levels in End-Stage Kidney Patients

Abstract: Effect of hemodialysis on phenylalanine distribution between the intracellular water of erythrocytes and the plasma obtained from patients with end-stage kidney was studied by fluorimetric measurements of phenylalanine concentration according to the method of Mc Caman and Robins. The measurements were performed twice: before and after 4 h of hemodialysis. It was found that the nondialyzed patients with end-stage kidney had higher than normal phenylalanine concentrations both in plasma and in the intracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Other neurotransmitters have a lso been studied: Sullivan reported increased levels of tryptophan in cerebrospina l fluid and plasma (10); several studies have reported reduced levels of y-aminobutyric acid and choline acetyl-transferase in CSF and brains of uraemic patients (11,12). Furthermore, plasma phenylalanine concentrations are raised (13), possibly due to the disorder in pterin metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Other neurotransmitters have a lso been studied: Sullivan reported increased levels of tryptophan in cerebrospina l fluid and plasma (10); several studies have reported reduced levels of y-aminobutyric acid and choline acetyl-transferase in CSF and brains of uraemic patients (11,12). Furthermore, plasma phenylalanine concentrations are raised (13), possibly due to the disorder in pterin metabolism.…”
Section: Introductionmentioning
confidence: 99%